The effect of using problem-solving strategies and self-revision in the teaching effectiveness of throwing the weight and the ability to develop creative thinking among students in the school year the first Faculty of Physical Education - University of Sa - Sadie, Hussein (Journal of Physical Education, 2012)
Therefore, the importance of this strategy stand out by making the students active during the lesson as well as its role in innovation and creativity, and the instruction using these strategies can develop students’ creativity, which in turn is the language of the current era, especially that the interest of psychologists has shifted from studying the student smart to study the creative student and the factors that contribute to creativity as the focus shifted from education Alelqaúa to innovative education, which depends on thinking and the means to meet the problems and provide creative solutions, and the effectiveness of throwing the weight is a events Games track and field, which calls for change and development and innovation in performance makes it imperative for the student possess creative thinking in order to reach a level of optimal performance.Hence, we can sum up the importance of this research with the following:ØMay disclose some of the results which show the effectiveness of their teaching effectiveness Strategies in throwing the weight and the ability to develop creative thinking.ØMay appoint officials the results of this research in the colleges and departments of physical education in the country to reconsider its educational Strategies currently used in the teaching effectiveness of throwing the weight and diagnose weaknesses to improve the effectiveness of education.The research aims to present the following: -ØDetect the effect of using problem-solving strategies and self-revision and learning approach in the teaching effectiveness of throwing the weight and the ability to develop creative thinking.ØDetect differences between problem-solving strategies and self-revision and learning approach in the teaching effectiveness of throwing the weight.ØDetect differences between the strategies of problem solving and self-revision and learning approach to creative thinking abilities.The researcher used the experimental method for suitability to the nature of research, and included a sample of the research (60) students of the school year, the first in the Faculty of Physical Education / University of Salahaddin, was distributed into three groups, by (20) students per group, the first experimental group studied according to problem-solving strategy, the second group studied according to a strategy of self-revision, and the control group studied according to the strategic learning approach (Prince).It was a homogeneity and Altkavo in variables (height, age, and weight) and some elements of physical fitness affecting the teaching effectiveness of throwing weight in addition to the technical performance and achievement of the event, and was relying on a scale Alvkir creative about the effectiveness of throwing the weight component of (74) paragraph, which was to make sure of its sincerity virtual offer a range of experts and professionals in the field of teaching methods and sport psychology, as was the test reconnaissance and after it has been giving lectures Tarevican been testing tribal performance art and achievement of the effectiveness of throwing the weight first and then the distribution of a measure creative thinking, have been implemented curriculum for a period of (5) weeks, and two teaching hospitals for each group, and the time of the module (90) minutes, and after the completion of the application of the curriculum has been testing a posteriori, after the analysis and processing of data statistically and extraction of statistical differences between pre and post tests in the research variables are all, The researcher came to the set of results which concluded Mayati: -ØThe curriculum of the educational problem-solving strategy according to a positive effect in learning the technical performance and the achievement of the digital level and the ability to develop creative thinking in the effectiveness of throwing the weight aggregates compared to the other.ØUse proven strategies to solve problems and self-revision Vaalithma in the variables (creative thinking, technical performance and achievement) in the effectiveness of throwing the weight.Øuse strategies than problem-solving and self-revision in a posteriori tests in the technical performance and achievement and the development of creative thinking of the effectiveness of throwing the weight when compared with the traditional strategy .